Therapeutic indications and metabolic effects of metreleptin in patients with lipodystrophy syndromes: Real‐life experience from a national reference network. Issue 8 (12th May 2022) - Mosbah, Héléna; Vantyghem, Marie‐Christine; Nobécourt, Estelle; Andreelli, Fabrizio; Archambeaud, Francoise; Bismuth, Elise; Briet, Claire; Cartigny, Maryse; Chevalier, Benjamin; Donadille, Bruno; Daguenel, Anne; Fichet, Mathilde; et al.
Abstract: Aim: To describe baseline characteristics and follow‐up data in patients with lipodystrophy syndromes treated with metreleptin in a national reference network, in a real‐life setting. Patients and Methods: Clinical and metabolic data from patients receiving metreleptin in France were retrospectively collected, at baseline, at 1 year and at the latest follow‐up during treatment. Results: Forty‐seven patients with lipodystrophy including generalized lipodystrophy (GLD; n = 28) and partial lipodystrophy (PLD; n = 19) received metreleptin over the last decade. At baseline, the median (interquartile range [IQR]) patient age was 29.3 (16.6‐47.6) years, body mass index was 23.8 (21.2‐25.7) kg/m 2 and serum leptin was 3.2 (1.0‐4.9) ng/mL, 94% of patients had diabetes (66% insulin‐treated), 53% had hypertension and 87% had dyslipidaemia. Metreleptin therapy, administered for a median (IQR) of 31.7 (14.2‐76.0) months, was ongoing in 77% of patients at the latest follow‐up. In patients with GLD, glycated haemoglobin (HbA1c) and fasting triglyceride levels significantly decreased from baseline to 1 year of metreleptin treatment, from 8.4 (6.5‐9.9)% [68 (48‐85) mmol/mol] to 6.8 (5.6‐7.4)% [51(38‐57) mmol/mol], and 3.6 (1.7‐8.5) mmol/L to 2.2 (1.1‐3.7) mmol/L, respectively ( P < 0.001), with sustained efficacy thereafter. In patients with PLD, HbA1c was not significantly modified (7.7 [7.1‐9.1]% [61 (54‐76) mmol/mol] at baseline vs. 7.7 [7.4‐9.5]% [61(57‐80) mmol/mol] at 1 year), and the decrease in fasting triglycerides (from 3.3 [1.9‐9.9] mmol/L to 2.5 [1.6‐5.3] mmol/L; P < 0.01) was not confirmed at the latest assessment (5.2 [2.2‐11.3] mmol/L). However, among PLD patients, at 1 year, 61% were responders regarding glucose homeostasis, with lower baseline leptin levels compared to nonresponders, and 61% were responders regarding triglyceridaemia. Liver enzymes significantly decreased only in the GLD group. Conclusions: In this real‐life setting study, metabolic outcomes are improved by metreleptin therapy in patients with GLD. The therapeutic indication for metreleptin needs to be clarified in patients with PLD.